1986
DOI: 10.1007/bf02343800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of passive heat adaptation and moderate sweatless conditioning on responses to cold and heat

Abstract: Two series of experiments were performed in physically untrained subjects. In series A (heat adaptation, HA), seven male subjects were adapted to dry heat (five consecutive days at 55 degrees C ambient air temperature (Ta) for 1 h X day-1) under resting conditions. Before and after HA, the subjects' shivering responses were determined in a cold test (Ta + 10 to 0 degrees C). In series B, eight male subjects underwent mild exercise training (five consecutive days at a heart rate, HR, of 120 b X min-1) under Ta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Indeed, Armstrong et al (1) and Cotter et al (6) failed to observe significant ṁ sw elevations after short-duration heat acclimation, while others have reported a more rapid sudomotor adaptation (9,14,38). Our long-term, controlledhyperthermia design was well suited to an evaluation of this adaptation pattern, and the current data show that only six exercise-heat exposures (controlled hyperthermia) were needed to elicit local sweat elevations from 33 to 69% (thigh-forearm; Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Indeed, Armstrong et al (1) and Cotter et al (6) failed to observe significant ṁ sw elevations after short-duration heat acclimation, while others have reported a more rapid sudomotor adaptation (9,14,38). Our long-term, controlledhyperthermia design was well suited to an evaluation of this adaptation pattern, and the current data show that only six exercise-heat exposures (controlled hyperthermia) were needed to elicit local sweat elevations from 33 to 69% (thigh-forearm; Fig.…”
Section: Discussionmentioning
confidence: 51%
“…(ii) Exercise-induced heat adaptation: Endurance exercise elevates muscle and deep tissue temperatures and, if this thermal load is applied regularly, heat adaptation will ensue 8) . This method may be used in three different ways, each of which can modify the resultant thermal strain: · Exercise under cool and temperate states: However, exercise in the absence of a T c elevation will not elicit heat adaptation 33) . · Exercise with a significant solar load.…”
Section: Heat Adaptationmentioning
confidence: 99%
“…Our previous study has shown that, in rats wvhich had been exposed to heat given for about 5 h in the last half of the dark phase for mnore than 10 days, T'or fell for 3-4 h during the period corresponding to the previous heat exposure time Schwennicke & Briick, 1976;Henane, 1981;Hessemer et al 1986) and animals (Bruiek et al 1970;Shido & Nagasaka, 1990). Shido & Nagasaka (1990) reported that, after subjection to heat for 5 h daily for 15 consecutive days, threshold T'or for tail skin vasodilatation tended to be lower in heat-acclimated rats than in non-acclimated animals.…”
Section: Discussionmentioning
confidence: 99%
“…In their experiments, the rats were exposed daily to heat in the light phase and the determination of threshold T,or was made during the same period of the heat exposure. Similarly, thermoeffector thresholds in humans were usually determined during the previous heat exposure periods (Schwennicke et al 1976;Henane, 1981;Hessemer et al 1986). Thus, previous reports are essentially consistent with the present observation which shows downward shifts in thermnoeffector thresholds during the period when the subjects had previously been exposed to heat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation